2007
DOI: 10.1007/s10452-007-9149-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Sciomyzidae (Diptera) across a transect at Skealoghan Turlough (Co. Mayo, Ireland)

Abstract: Sciomyzid flies, which have potential as bio-indicators, were sampled by sweep-net surveys at a turlough in the west of Ireland. Turloughs are ephemeral wetlands (unique to Ireland), which flood from groundwater in winter and empty in the summer, during that time, they are frequently grazed.The weekly survey consisted of ten linear sweeps (5 m 9 1 m) in each of six homogeneous and contiguous vegetation zones throughout the summer of 2004. The fauna was dominated by univoltine species with Ilione albiseta being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…Sweep net sampling also showed a significant (P=0.005) difference between infill and wetland, with P. coryleti being a significant (P<0.005) indicator species for wetland. These findings support previous studies showing that sciomyzids display limited movement and are habitat specific (Speight, 2004;Vala & Brunel, 1987;Williams et al, 2009Williams et al, , 2010.…”
Section: Sciomyzid Communitiessupporting
confidence: 92%
See 3 more Smart Citations
“…Sweep net sampling also showed a significant (P=0.005) difference between infill and wetland, with P. coryleti being a significant (P<0.005) indicator species for wetland. These findings support previous studies showing that sciomyzids display limited movement and are habitat specific (Speight, 2004;Vala & Brunel, 1987;Williams et al, 2009Williams et al, , 2010.…”
Section: Sciomyzid Communitiessupporting
confidence: 92%
“…With this in mind, we concentrated on wetland biological groups such as plants which are sensitive to chemical changes in their environment (LaPaix et al2009;Pardo et al, 2011) and Diptera (families and morphospecies), shown to be influenced by vegetation structure (Hughes et al, 2000;King & Brazner, 1999;Whiles and Goldowitz, 2001). In particular, we identified marsh flies (Diptera: Sciomyzidae), to species level since they have been shown to reflect a range of wetland conditions (Murphy et al, 2012;Speight, 1986;Williams et al, 2009Williams et al, , 2010. While plants are frequently used in isolation to assess habitats, we included invertebrate groups in this study given that, apart from charismatic invertebrate species such as butterflies, policy makers can often be unaware of problems associated with general invertebrate conservation (Cardoso et al, 2011).…”
Section: Construction and Demolition Wastementioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, animal ecologists seldom use EIVs to address ecological questions, and only a few researchers have tested this approach so far. Significant relationships have been found between EIVs and the diversity of Sciomyzid flies [16], butterflies [1720] and molluscs [21]. In addition, EIVs are sometimes used to characterize the ecological properties of habitats of studied animal assemblages, e.g.…”
Section: Introductionmentioning
confidence: 99%